Semiotic Analysis Roland Barthes of The Movie “Hachiko: A Dog’s Tale” - Firlianty, Lie Fika (Universitas Bunda Mulia, 2024)
Movies serve not only as entertainment but also as a means of communication to conveying moral, social, and religious values. There are several films inspired by true stories, including interactions between humans and animals that are compelling to narrate. One such film is